(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The paper focuses on the Comprehensive Economic and Trade Agreement between Canada and the European Union and its Member States, signed in Brussels on 30 October 2016 (CETA), on the investor-state dispute settlement mechanism contained therein and its compatibility with the EU legal system. It analyses the question of autonomy of the EU legal system and the difficult relationship between the Court of Justice of the European Union (CJEU) and other international jurisdictions. It identifies the compatibility conditions of different dispute settlement mechanisms developed in the CJEU’s earlier case law; e.g. the allocation of powers fixed by the treaties founding the EU must not be affected, the primacy of EU law and its direct effect must be assured, the mechanism must preserve the role of national courts and tribunals to ensure the full application of EU law in all Member States, the CJEU’s exclusive jurisdiction to give binding interpretations of the EU law must be assured and any action by the international tribunal must not have the effect of binding the EU and its institutions, in the exercise of their internal powers. In its opinion 1/17, the CJEU softened its approach. The paper examines how different the Investment Court System under CETA is.